2019
DOI: 10.1116/1.5115769
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of poly-2-vinylpyridine—A polymer for area selective deposition techniques

Abstract: Thin films of OH terminated poly-2-vinylpyridine (P2VP-OH), a polymer with potential for infiltration mediated thin film deposition, area selective deposition (ASD) and small feature size development via block copolymer (BCP) self-assembly, has been studied with hard X-Ray photoelectron spectroscopy (HAXPES). From the N 1s and C 1s core level spectra, accurate values for the binding energy positions of the species present in the films were obtained, providing clear evidence for signals associated to pyridine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…81,82 Post UV/ ozone exposure, there is an increase in the SiO 2 peak because of reduced attenuation of the substrate signal. Before UV/ ozone exposure, the N 1s region (Figure 5c) has a peak at ≈399 eV associated with CN−C pyridine bonds, 83,84 while after UV/ozone exposure, the pyridine signal is absent (within XPS detection limits), indicating total removal/conversion of the brush material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 Post UV/ ozone exposure, there is an increase in the SiO 2 peak because of reduced attenuation of the substrate signal. Before UV/ ozone exposure, the N 1s region (Figure 5c) has a peak at ≈399 eV associated with CN−C pyridine bonds, 83,84 while after UV/ozone exposure, the pyridine signal is absent (within XPS detection limits), indicating total removal/conversion of the brush material.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Before and after UV/ozone exposure, the Si–O and Ti–O peaks are observed at ≈532.7 and ≈530.7 eV, respectively, consistent with literature values. , Post UV/ozone exposure, there is an increase in the SiO 2 peak because of reduced attenuation of the substrate signal. Before UV/ozone exposure, the N 1s region (Figure c) has a peak at ≈399 eV associated with CN–C pyridine bonds, , while after UV/ozone exposure, the pyridine signal is absent (within XPS detection limits), indicating total removal/conversion of the brush material.…”
Section: Results and Discussionmentioning
confidence: 99%
“…TEM and EDX cross sections of the fabricated P2VP-OH films in the outlined process has previously revealed that the resultant polymer films are ~4 nm in thickness [12]. The images in Figure 3 show the resultant cross sections arising from the ALD and oxygen plasma process.…”
Section: Tem and Edxmentioning
confidence: 92%
“…Because of the interest in PVP as a potential acceptor, recent work has shown progress in its use via rapid, high-quality grafting of the polymer as a brush layer, and its infiltration with Al through a liquid phase approach [11]. Our previous studies have concentrated on the surface characterisation of these P2VP-OH brushes [12], and the capacity that these films have in facilitating infiltration via a Cu salt (liquid phase) inclusion process [13].…”
Section: Introductionmentioning
confidence: 99%
“…They can be used for ASD to facilitate selective patterning of large substrate areas [ 11 , 17 ]. For example, in poly(2-vinylpyridine) (P2VP) or poly(4-vinylpyridine) (P4VP) brushes, it is the presence of an unshared electron pair on the nitrogen atom of the pyridine ring that facilitates coordination bonding with various metal species [ 66 ]. Conversely, Polymer brushes such as polystyrene (PS) can be used for surface deactivation to block metals adhering to the substrate [ 17 , 21 , 67 , 68 ].…”
Section: Bottom-up Versus Top-down Lithographymentioning
confidence: 99%